Assessment of different rates of NPK fertilizer on the growth and yield components of two exotic okra (Abelmoschus esculentus L.) western urban of Sierra Leone - Ngegba, P. M.; Kanneh, S. M.; Quee, D. D. (International Journal of Horticultural Science, 2020)
The experiment was conducted in an Inland Valley Swamp during the dry spell of 2017 laid out in a randomized complete block design (RCBD) three replications at the Kabala Horticultural Crops Research Centre (KHCRC) cropping site, Ogoo Farm of the Sierra Leone Agricultural Research Institute (SLARI), Freetown, Sierra Leone. Raised beds measuring 5m x 1m (6 m2) with a 1m furrow between beds. Inter and intra row spacing of 75 cm by 50 cm with two rows per bed and two seeds per hills were directly sown. The treatments constituted NPK 15:15:15 at the rate of 0, 90, 120 and 150 kg/ha designated as T1, T2, T3 & T4 and Two hybrids of okra were used as experimental materials obtained from Indo-American Hybrid Seed Company, India; Okra-WASA-HyOKR-1 and Okra-WASA-HyOKR-2. Seeds were treated with Thiram Poison for longevity. Result indicates T2 (25.2; 35.1 cm) and T4 (56.9 cm) treatments recorded tallest plant heights followed by T2 (24.0, 34.4 & 50.1 cm), while T1 (18.8, 28.4 & 33.3 cm) had the shortest plant heights at 4, 8 & 10 Week After Planting respectively. Similarly, T4 & T2 (38.9, 65.5 & 44.8 cm) exhibited the largest SG and T1 (21.7, 33.0 & 52.0 cm) the least values at 4, 8 & 10 Week After Planting. While, the widest and narrowest LA at 4, 8 & 10 Week After Planting was observed in T3 (131.3, 135.0 & 158.5 cm2) and T1 (120.8, 121.8 & 128.1 cm2). With respect to yield and yield components, the longest (22.0 cm) and heaviest (112.7 g) fruit were recorded by T3 followed by T2 (19.1 cm & 101.3 g) with T1 having the shortest (11.7 cm) and lightest (52.3 g). The width of pod in T3 (31.2 cm) was greater than the rest of treatments and as usual, T1 indicated the least value (14.6 cm) respectively. The average NP produced plant-1 was shown by T2 & T3 (4.0) with the least of fruit produced by T1 (2.0). Also, 100 seed weight, T3 (106.7 g) weighted the highest followed by T2 (103.3 g), while T1 (60.3 g) accounted for the lowest seed weight. Conclusively, the two materials are adaptable to the climatic conditions of Sierra Leone (Western area). Hence further evaluation required across vegetable growing zones.